The Hirnantian-Early Llandovery transition sequence in the Paraná basin, Eastern Paraguay - Cingolani, Carlos Alberto (2011)
The Lower Paleozoic Itacurubí Group (Harrington, 1972) is exposed in the western border of the intracratonic Paraná Basin of eastern Paraguay (Fig. 1). This group (c. 350 m thick) includes from base to top the Eusebio Ayala, Vargas Peña and Cariy siliciclastic formations. It was traditionally assigned to the Llandovery (e.g. Harrington, 1950; Dyck, 1991; Benedetto et al., 1992; Benedetto, 2002; Galeano Inchausti and Poiré, 2006; Uriz et al., 2008a, 2008b and references therein) based on a marine fossil record mainly of graptolites, shelly fauna, and palynofacies assemblages. The new records of graptolites and some trilobites from the Eusebio Ayala Formation, exposed in clay quarries to the east of Asunción allow the comparison with other sequences bearing similar faunal associations known in west Gondwana. These records are discussed here, taken into account that the mentioned interval was a relevant paleobiogeographical time slice during the Lower Paleozoic (Cocks, 2001).